Thermal stability and pyrolysis behavior of an efficient fire-retarded polypropylene containing allylamine polyphosphate and pentaerythritol - Xiao, Dan; Gohs, Uwe; Wagenknecht, Udo; Voit, Brigitte; Wang, De-Yi (Thermochimica Acta, 2022)
A novel fire-retardant system containing of allylamine polyphosphate/pentaerythritol (AAPP/PER) was used to enhance fire safety of polypropylene (PP). A series of PP with AAPP and PER were mixed via melt blend. Afterwards PP-AAPP/PER system was treated by electron-beam irradiation to increase its thermal stability. The degradation and fire behavior of PP-AAPP/PER system was systematically investigated. The results showed that the LOI testing of PP with 20 wt%AAPP/PER was greatly increased and passed UL 94 vertical testing V-0 rating level. Moreover, the cone-calorimeter testing showed that heat release, smoke produce as well as toxic gasses production of PP-AAPP/PER system largely decreased. Incorporation of PER and AAPP was very efficient for enhancing the fire safety of PP composites due to relatively more compact of char residues. Moreover, the sustainable electron-beam irradiation without any use of thermal stabilizers was used to improve the thermal performance of PP-AAPP/PER system.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electron beam irradiation; Fire-retardant properties; Intumescent flame retardant; Pyrolysis behavior; Thermal behavior